(untitled) (Research, Society and Development, 2021)
We aimed to study hematological responses of Oreochromis niloticus experimentally exposed to the contaminated water of the Santos-São Vicente Estuary, testing hypotheses that exposure time to estuarine water promotes deleterious effects on hematological parameters and evaluating the use of erythrocytes and leukocytes alterations as environmental biomarkers. Estuarine water was collected from Largo da Pompeba. For the biological assay, 28 juveniles of O. niloticus (red strain) of both genders were randomly selected from commercial pisciculture. For the biological assay, 28 juveniles of O. niloticus of both sexes were randomly selected from commercial fish farms. The juveniles were kept in estuarine water for 72 and 120 hours and, after exposure, blood was collected by puncture of the caudal vein to determine total erythrocytes, hemoglobin concentration, hematocrit, hematimetric indices and total leukocytes, as lymphocyte, neutrophils, monocytes, eosinophils, and basophils were quantified by blood extensions. To test exposure overtime on hematological variables, we performed a two-factor Multivariate Analysis of Variance. Exposure for 72 hours resulted in immunosuppression as seen by the reduced counts of neutrophils, monocytes, and lymphocytes in the bloodstream, whereas after 120 hours the immune system was stimulated with the increase of all leukocyte cell types. Exposure to estuarine water resulted in marked changes in the leukocyte count of O. niloticus, demonstrating that alterations in white blood cells might be more sensitive biomarkers than red blood parameters.